PENGARUH PENGENDALIAN INTERN PENJUALAN DAN SISTEM INFORMASI AKUNTANSI PENJUALAN TERHADAP KUALITAS INFORMASI PENJUALAN - Anisa Andiani; Wawan Sukmana; Intan Rahayu (LP2M Universitas Perjuangan Tasikmalaya, 2021)
The objectives of this research was to determine the internal sales control, sales accounting information systems and the quality of sales information at medium and large companies in the city of Tasikmalaya. As well as analyzing the effect of internal control of sales and sales accounting information systems on the quality of sales information at large and medium companies in the city of Tasikmalaya. The research method used in this study is a survey method, while the type of data used in this study is primary data. The object of this research is the City of Tasikmalaya Large and Medium Enterprises, with the sampling technique using the area sampling method. The data analysis technique used is multiple regression analysis and hypothesis testing. The results of this test prove that internal sales, sales accounting information systems and the quality of sales information at medium and large companies in Tasikmalaya City are good. The results also show that sales internal control and sales accounting information systems have a significant effect on the quality of sales information at large and medium companies in Tasikmalaya City. It is preferable that Large and Medium in Tasikmalaya City further improve the quality of internal sales controls and sales accounting information systems in order to be able to improve the quality of sales information optimally.